1986
DOI: 10.1111/j.1476-5381.1986.tb11117.x
|View full text |Cite
|
Sign up to set email alerts
|

Tetrodotoxin‐sensitive, K+‐induced relaxation of guinea‐pig isolated trachealis in the presence of Ca2+‐entry blocking drugs, Ca2+‐free solution and after polyamine exposure

Abstract: 1 We have previously observed a paradoxical relaxant effect of K+ on guinea-pig isolated trachealis after exposure to polyamines. The purpose of the present study was to evaluate whether the relaxation involved a reduction in the entry ofextracellular Ca2+. We therefore investigated the effect of K+ in the presence of Ca2+-entry blocking drugs and in the presence of Ca2+-free solution. 3 A relaxation in response to K+ was also observed in Ca2+-free solution, (with tone induced by methacholine), an effect not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…However, the few studies in airway physiology have revealed contrasting results. Chideckel and colleagues (32,33) found that spermidine and spermine induced transient relaxation of guinea pig tracheal smooth muscle, and that subsequent exposures resulted in diminished responses, suggesting tachyphylaxis and possibly neurogenic mechanisms. In contrast, Bueb and colleagues (34) demonstrated contractile effects of spermidine and spermine on epithelial-denuded rat tracheal segments.…”
Section: Polyamines and Airways Responsivenessmentioning
confidence: 99%
“…However, the few studies in airway physiology have revealed contrasting results. Chideckel and colleagues (32,33) found that spermidine and spermine induced transient relaxation of guinea pig tracheal smooth muscle, and that subsequent exposures resulted in diminished responses, suggesting tachyphylaxis and possibly neurogenic mechanisms. In contrast, Bueb and colleagues (34) demonstrated contractile effects of spermidine and spermine on epithelial-denuded rat tracheal segments.…”
Section: Polyamines and Airways Responsivenessmentioning
confidence: 99%
“…It has been postulated that high K+-induced relaxation in guinea-pig trachea is secondary to release of a non-adrenergic, non-cholinergic inhibitory transmitter(s) (Chideckel et al, 1986). The release by high K+ is sensitive to TTX in that preparation.…”
Section: Discussionmentioning
confidence: 99%